The Dynamics of Makondoro’s Arabic-Islamic Pedagogy in Western Nigeria - Alagunfon, Sulaiman Adewale (Islamic Studies, 2023)
Zumrat al-Mu’minīn (the Believers’ Group), also known as Makondoro, is a group of conservative Arabic-Islamic scholars in Yorubaland, a region in Western Nigeria. When studying, teaching, and professing their Arabic and Islamic knowledge, they utilize a pedagogical method of discipleship that links students with their teachers and shapes their learning. They have devised strategies to retain this method, such as creating epistemological networks that have earned them authority in Yorubaland since the middle of the twentieth century. Although modernization has held sway in Arabic-Islamic education of the region post-independence, the Makondoro maintain and preserve their ways. Drawing on ethnographic research, participant observation, and personal interactions with scholars and students of the Makondoro, this article seeks to understand their pedagogical dynamics in the last fifty years when they came into prominence in major cities of Western Nigeria.